Peruvian Amazonian filmmaking in the first half of the 20th century - Boggio Lozada, Verónica (2019)
The history of Peruvian cinema is still an unfinished narrative ridden with lost pages. This article is an initial effort that elaborates a descriptive chronology of the films made in the Peruvian Amazon from its beginnings to the first half of the 20th century. It goes through the first recordings and projections and then highlights the role of the pioneers of the cinematrographic record of this area, including Peruvians, and foreigners according to their historical relevance. It also explores the historical context in which these productions were created.